The impact of oil supply surprises on maritime transport: a temporal and sectoral analysis - Tarkun, Savas (Springer, 2025)
This study investigates how oil supply surprises affect maritime transport across time and sectors. Using the K & auml;nzig (Am Econ Rev 11(4):1092-1125, 2021. https://doi.org/10.1257/AER.20190964) approach, we identify shocks from OPEC announcements and examine their effects on shipping indices through the Barun & iacute;k and K & rcaron;ehl & iacute;k (J Financ Econom 16(2):271-296, 2018. https://doi.org/10.1093/jjfinec/nby001) frequency connectedness model, Gabauer and Gupta's (Econ Lett 171:63-71, 2018. https://doi.org/10.1016/j.econlet.2018.07.007) external connectedness framework, and impulse response analysis. Results show that oil shocks affect tanker indices (BDTI, BCTI) more than dry bulk (BDI). In the medium term, spillovers reach up to 0.33% for BCTI and 0.19% for BDTI, but only 0.05% for BDI. Brent-based shocks transmit over 5.4% of external information during crisis periods. Impulse responses confirm that shock effects are short-lived and economically minor (0.0005-0.001), indicating short-term resilience. These findings reveal asymmetric, time-varying sensitivities across shipping segments. The study offers policy recommendations to enhance resilience in freight markets facing oil-related volatility.
Keywords: Oil supply surprises; Maritime transport; Freight rates; Frequency connectedness; External connectedness; Energy markets; G15; L91; Q41